BUDAYA PROFETIK PUISI TAUFIK ISMAIL - Salfi Faridoni (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This article is about prophetic culture on Taufik Ismail poems.The interpretation method is used and it is related to the reality in orderto make it alive. There are three items which are found in the poem;humanism, liberation, and transendence. Those three principles lead allhuman to be closer to God.